TMIC-58. THE CELLULAR AND MOLECULAR BASIS FOR MESENCHYMAL TRANSFORMATION IN GLIOMAS. (11th November 2019) - Comba, Andrea; J Dunn, Patrick; E Argento, Anna; Kadiyala, Padma; Motsch, Sebastien; Kahana, Alon; E Kish, Phillip; Castro, Maria; Lowenstein, Pedro
Abstract: Mesenchymal gliomas are the most aggressive tumors that carry the worst prognosis. The origins of mesenchymal cells within brain tumors, remains poorly understood. They could originate either from invading mesenchymal cells, from perivascular smooth muscle actin+ cells, or from a mesenchymal transformation of tumor cells. Identifying the origin and function of mesenchymal cells within gliomas is essential as these cells contribute to increased glioma aggressiveness and tumor progression. In this study we used human biopsies and implantable and genetically engineered mouse models (GEMM) of GBM to study tumor mesenchymal transformation. GBM implantable models were used to analyze the molecular landscape by laser microdissection followed by RNA-Seq and bioinformatics analysis. Time lapse confocal imagining was implemented to analyze GBM cells dynamics. Our results indicate the existence of a complex intratumoral and peritumoral dynamic organization of glioma cells (i.e., Oncostreams). Multicellular structures of elongated cells compatible with mesenchymal differentiation. These structures play important roles in intratumoral movements, peritumoral invasion of normal brain, and overall glioma progression. We also show that oncostreams are molecularly distinct and display increased expression of mesenchymal genes such as Col1a1. Knocking down of Col1a1 in a GEMM of aggressive gliomas reduced tumor progression and significantly increased animal survival. Histological examination confirmed absence of Col1a1, and absence of morphologically identifiable oncostreams. Our results show that tumor cells, especially within oncostreams, display a fibroblastic-like morphology and express proteins typical of mesenchymal cells. The knockout of Col1a1 from tumoral cells eliminated oncostreams from tumors and delayed tumor progression. These data suggest that tumor cells expressing mesenchymal genes regulate the organization of mesenchymal multicellular structures, and determine glioma progression. We propose that inhibiting mesenchymal transformation of glioma cells will assist in the treatment of glioblastoma.